SYNERGISTIC EFFECTS OF TABATA HIGH-INTENSITY INTERVAL TRAINING AND ELECTRO MUSCLE STIMULATION ON BODY COMPOSITION AND PERFORMANCE ADAPTATIONS AMONG UNIVERSITY STUDENTS - Zainudin, Aisyah; Othman, Syuhadah; Irin, Eshelvana Elve; Nazarudin, Mohamad Nizam (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study examined the combined effects of Tabata high-intensity interval training (HIIT) and electro muscle stimulation (EMS) on body composition and performance adaptations among university students. Sixty physically active participants (30 males and 30 females) were randomly assigned into four groups: Tabata + EMS (T-EMS), Sprint Interval Training + EMS (SIT-EMS), Tabata only (T-HIIT), and Sprint Interval Training only (SIT-HIIT). Over eight weeks, participants trained three times per week, following progressive-intensity protocols. Repeated-measures ANOVA revealed significant improvements in muscle mass, VO₂ max, and fat oxidation across all groups, with the T-EMS group showing the greatest gains (p < 0.05). Males exhibited greater hypertrophy and improvements in VO₂ max, while females demonstrated superior autonomic recovery and fat oxidation. The findings support the idea that integrating EMS with Tabata HIIT amplifies neuromuscular activation, endurance capacity, and body composition outcomes beyond those of traditional HIIT protocols. These results highlight the potential of EMS-enhanced Tabata training as a time-efficient and physiologically superior method for improving fitness in young adults.